Improving Students' Speaking Ability Though Problem Solving Strategy at the ninth grade of SMP Negeri 2 Momunu - A. Gama, Jusniati; Jusuf, Harni; Akhmad, Zulkifli (Journal of English Teaching and Linguistic Issues (JETLI), 2023)
This study aims to improve students' speaking skills using Problem Solving Strategy. This study is a classroom action research with the subject is the ninth students of SMP Negeri 2 Momunu Buol Regency, central Sulawesi Province. The study uses observations sheets of teacher and student activity and test to get the data. In this study, for the data analysis, researchers used a speaking assessment rubric consisting of 5 aspects such as comprehension, fluency, grammar, vocabulary and pronunciation. Researchers found that in the first cycle the increase in students' speaking skills that reached the learning completeness criteria of 70 was 11 (44%) students and those who had not reached the learning completeness criteria were 14 (56%) with an average score of 69.44 the highest score reached 80 and the lowest score was 64. Then in the second cycle there was a significant increase where the standard of completeness of learning outcomes, especially in speaking skills, reached 24 (96%) students and students who had not reached the learning completeness criteria were 1 (4%) student. While the average score of students obtained in the second cycle was 81.52 with the highest score reaching 92 and the lowest score 68. Based on this research, the researcher can draw the conclusion that the application of the problem solving strategy learning model is able to increase student activeness in discussion groups therefore students' speaking skills also increase.